Kemampuan Pemahaman Siswa Melalui Pembelajaran Daring Menggunakan Metode Pembelajaran Visual, Auditory, dan Kinesthetic - Rosdiani, Dini; Maulana, M.; Irawati, Riana (Jurnal Pena Ilmiah, 2021)
Understanding ability is a basic ability that students need to have so that they can develop other abilities in learning. Through online learning using visual, auditory, and kinesthetic learning methods, the teacher tries to optimize learning by utilizing student learning styles, so that learning can develop students' understanding abilities. The purpose of this research is to find out how the students' understanding ability after learning is given and to know how to implement online learning using visual, auditory, and kinesthetic learning methods. Pre-experiment one group pretest-posttest is the research method used in this study. The population in this study were all fourth-grade students of Public Elementary Schools in Sumedang Regency in the 2020/2021 academic year, while the samples were fourth-grade students of SDN Lembursitu and SDN Tenjolaya. Based on the results of the research that has been carried out, the conclusions obtained are: 1) Students' understanding ability in online learning with visual, auditory, and kinesthetic methods has increased. 2) The implementation of online learning using visual, auditory, and kinesthetic learning methods as a whole went well.